A systematic review of brain imaging findings in neurological infection with Japanese encephalitis virus compared with Dengue virus. (June 2022) - Pichl, Thomas; Wedderburn, Catherine J; Hoskote, Chandrashekar; Turtle, Lance; Bharucha, Tehmina
Highlights: This review investigates neuroimaging in Japanese encephalitis and dengue. Thalamic lesions frequently occurred in both Japanese encephalitis and dengue encephalitis. Immunoglobulin M in the cerebrospinal fluid was associated with thalamic lesions in Japanese encephalitis but not in dengue. In dengue cases diagnosed with antigen or polymerase chain reaction tests, brain lesions were common. Magnetic resonance imaging revealed more brain lesions than x-ray computed tomography. Abstract: Objectives: Japanese encephalitis virus (JEV) and dengue virus (DENV) represent important causes of encephalitis in Asia. Brain imaging may provide diagnostic clues about the etiology of infectious encephalitis. We performed a systematic review of brain imaging findings in Japanese encephalitis (JE) and DENV neurological infection (dengue) to identify characteristic lesions. Methodology: Five databases were searched. We included all study types and imaging techniques. Laboratory methods were categorized using diagnostic confidence levels. Imaging data were synthesized, and focal findings are presented as proportions for JE and dengue and for subgroups based on diagnostic confidence. Principal findings: Thalamic lesions were the most reported magnetic resonance imaging finding in both diseases but appeared to occur more often in JE (74% in 23 studies) than dengue (29.4% in 58 studies). In cases diagnosed with antigen or nucleic acid tests, thalamic lesions were reported frequently in both JE (76.5% in 17 studies) and dengue (65.2% in 23 studies). Significance: The results suggest that thalamic lesions frequently occur in both JE and dengue encephalitis. No radiological findings were found to be pathognomonic of either disease. Although brain imaging may support a diagnosis, laboratory confirmation with highly specific tests remains crucial.